GoDonnie: A robot programming language for teaching people who are visually impaired - Oliveira, Juliana Damasio; Campos, Márcia de Borba; Amory, Alexandre M.; Bordini, Rafael H. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2019.1181, 2019)
Recent work indicates that many programming environments and languages are difficult for people who are visually impaired to use, which may contribute to excluding them from a professional career in computing. This work aims to create and evaluate the use of a programming language called GoDonnie for students who are visually impaired. We developed a programming language that students use to simulate a robot’s behavior. We also introduce two usability studies that were conducted with end-users. The initial results indicate that our programming language is easy to learn by beginners and experienced programmers alike. In addition, users report high levels of enjoyment when programming in GoDonnie.